Pembelajaran dan Pemanfaatan Blog Bagi Puskesmas-Puskesmas di Lingkungan Kota Padang - Nusa Putra, Hendra; Wisandra, Ade; Alfauzain, Alfauzain (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This community service activity aims to train community health center staff to create blogs as a medium of communication and information for the community. The benefits include increasing staff knowledge about blogging, facilitating access to health information and public health center services via the internet, as well as strengthening the relationship between the Community Health Centers in Padang City and STIKES Dharma Landbouw Padang. Activities are carried out online using Zoom with explanations, blog practice, and discussions. The results include permit preparation, equipment preparation, and presentation via Zoom. The majority of public health centers in Padang City do not yet have effective communication media, but with blogs, they can convey health program information, schedule services, and interact directly with the community. This activity succeeded in increasing the technical skills of community health center staff in creating and managing blogs, as well as increasing public awareness about health. The use of blogs also supports the adoption of digital technology in the health sector and improves service quality.